2017
DOI: 10.1007/s00294-017-0717-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mitochondrial dynamics on mitochondrial genome stability

Abstract: Mitochondria are dynamic organelles that fuse and divide. These changes alter the number and distribution of mitochondrial structures throughout the cell in response to developmental and metabolic cues. We have demonstrated that mitochondrial fission is essential to the maintenance of mitochondrial DNA (mtDNA) under changing metabolic conditions in wild-type Saccharomyces cerevisiae. While increased loss of mtDNA integrity has been demonstrated for dnm1-∆ fission mutants after growth in a non-fermentable carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Mitochondrial repair and recycling are often referred to as mitochondrial dynamics: an elegant process of fusion (joining), fission (separation), biogenesis (synthesis of new mitochondria) and mitophagy (clearance of dysfunctional mitochondria) to adapt to a constantly changing environment (51). As this mechanism is critical to mitochondrial function and thereby cellular and tissue health, any alteration to such a process has direct consequences on organ function (51,67,109). Recently it has been shown that changes to mitochondrial dynamics resulting in fragmentation, swollen and large mitochondria which cannot undergo mitophagy are indicative of ageing (51).…”
Section: Mitochondrial Dynamics and Placental Ageingmentioning
confidence: 99%
“…Mitochondrial repair and recycling are often referred to as mitochondrial dynamics: an elegant process of fusion (joining), fission (separation), biogenesis (synthesis of new mitochondria) and mitophagy (clearance of dysfunctional mitochondria) to adapt to a constantly changing environment (51). As this mechanism is critical to mitochondrial function and thereby cellular and tissue health, any alteration to such a process has direct consequences on organ function (51,67,109). Recently it has been shown that changes to mitochondrial dynamics resulting in fragmentation, swollen and large mitochondria which cannot undergo mitophagy are indicative of ageing (51).…”
Section: Mitochondrial Dynamics and Placental Ageingmentioning
confidence: 99%
“…The structural diversity of the recombinant mitochondrial genomes can be ascribed to recombination events at random positions. The intensifying research into yeast mitochondrial biology (e.g., Wu et al, 2015;Higuchi-Sanabria et al, 2016;Pernice et al, 2016Pernice et al, , 2018Chakraborty et al, 2017;Guaragnella et al, 2018;Prevost et al, 2018;Ling et al, 2019;Dhar et al, 2019;Peris et al, 2019) will surely provide novel tools for the deciphering of the complexity of the mechanisms underlying the transmission of the mitochondrial genomes into the hybrid bud formed on the zygote and their subsequent evolution.…”
Section: Hybrid Homoplasmymentioning
confidence: 99%
“…Dnm1 is recruited to mitochondria by co-factors: Fis1, a protein in the mitochondrial outer membrane (Mozdy et al 2000), and Mdv1 that binds to both Fis1 and Dnm1 and brings them together (Cerveny and Jensen 2003; Cerveny et al 2001; Karren et al 2005; Tieu and Nunnari 2000; Tieu et al 2002). Saccharomyces cerevisiae deletion mutants in DNM1, FIS1 or MDV1 display a mitochondrial fission defect, resulting in the formation of long, hyper-connected mitochondria, and also have some other cellular phenotypes related to fitness, as well as organelle and membrane structure and contacts (Dimmer et al 2002; Elbaz-Alon et al 2014; Gorsich and Shaw 2004; Kanki et al 2009; Prevost et al 2018; Qian et al 2012). Deletion of CAF1 , a paralog of MDV1 , does not cause a fission defect by itself, but it potentiates the defect of mdv1 mutants (Griffin et al 2005).…”
Section: Mitochondrial Fission In Pathogenic Fungal Speciesmentioning
confidence: 99%